Pentingnya Pembelajaran Public Speaking dan Peranannya dalam Mengembangkan Kemampuan Berbicara di Depan Umum Bagi Anggota Dharma Wanita di Dharma Wanita Persatuan Dinas Pertanian dan Ketahanan Pangan Kabupaten Banyumas - Poppy Fitrijanti Soeparan; Nugrah Leksono Putri Handayani (Gemawisata: Jurnal Ilmiah Pariwisata, 2024)
Like communication itself, Public Speaking, which is part of it, has an important role in social life. All individuals, whether in daily life or in organizations, need to ensure communication can run well. Communication itself can occur between individuals or between individuals and many people. This is where Public Speaking plays its role.Public Speaking is the ability to speak in public. Its not just about talking , but you need rules and knowledge to be able to do Public Speaking well, interesting, smooth. So it is very necessary for individuals, both for their own interests and the interests of the organization, to understand and master the Public Speaking. In relation to Dharma Wanita, Public speaking knowledge is very important to develop Public Speaking skills.